Governance of Vietnam's Financial Institutions in Accordance with International Standards until 2020 - Tram, Thi Xuan Huong (University of Economics Ho Chi Minh City, 2023)
In this article, using a combination of risk-related factors, we address the governance of financial institutions, mainly Vietnam’s commercial banks, in light of such international standards as of Basel II and III. Additionally, we employ multiple regression approach to shed light on the effect of each type of risk on bank performance and propose a few recommendations for effectively governing the commercial banking system of Vietnam until 2020.